2020
DOI: 10.1101/2020.09.30.318972
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LY-CoV555, a rapidly isolated potent neutralizing antibody, provides protection in a non-human primate model of SARS-CoV-2 infection

Abstract: SARS-CoV-2 poses a public health threat for which therapeutic agents are urgently needed. Herein, we report that high-throughput microfluidic screening of antigen-specific B-cells led to the identification of LY-CoV555, a potent anti-spike neutralizing antibody from a convalescent COVID-19 patient. Biochemical, structural, and functional characterization revealed high-affinity binding to the receptor-binding domain, ACE2 binding inhibition, and potent neutralizing activity. In a rhesus macaque challenge model,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
167
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(174 citation statements)
references
References 24 publications
4
167
1
Order By: Relevance
“…In preclinical models of Covid-19, the use of LY-CoV555 improved clinical outcomes. 5 A dose of 7000 mg was chosen on the basis of pharmacokinetic and preliminary safety data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In preclinical models of Covid-19, the use of LY-CoV555 improved clinical outcomes. 5 A dose of 7000 mg was chosen on the basis of pharmacokinetic and preliminary safety data.…”
Section: Methodsmentioning
confidence: 99%
“…To understand the possible role of neutralizing monoclonal antibodies and other antiviral interventions in patients who are hospitalized with Covid-19, the National Institutes of Health established the ACTIV-3/TICO (Therapeutics for Inpatients with Covid-19) platform 4 for the efficient conduct of trials. The first trial within the TICO platform was a comparison of LY-CoV555 5 and placebo. We report here the preliminary results of this trial.…”
mentioning
confidence: 99%
“…Amongst the seven animal studies, four looked at the use of antibodies [ [21] , [22] , [23] , [24] ]. All found an effect although they did not report comparable outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…All found an effect although they did not report comparable outcomes. Jones et al [ 21 ] reported reduced viral replication, Li et al and Tortorici et al reported high prophylactic efficacy [ 22 , 24 ], while rogers et al reported a 50% reduction in disease as measured by weight loss [ 25 ].The three remaining animal studies looked at the effect of HCQ alone [ 25 , 26 ] or compared to favipiravir [ 25 ]. All three demonstrated no observed effect of HCQ but Kaptein et al did show that favipiravir significantly reduced infectious titre [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Convalescent plasma is routinely used for patients with COVID-19 but recombinant antibodies need more in vitro and in vivo evaluation to investigate their prophylactic and therapeutic efficacy. Fascinatingly, LY-CoV555, a monoclonal antibody derived from a recovered COVID-19 patient (NCT004497987) ( Jones et al, 2020 ) and REGN-COV-2, a combination of two monoclonal antibodies targeting two regions of S protein (NCT04452318) ( Baum et al, 2020 ) are being progressed to phase 3 clinical trial ( Table 1 ).…”
Section: Coronaviridae Sars-cov-2mentioning
confidence: 99%